حدوث العالم عند الإمام النّسفيّ: Impermanence of Nature according to al-Imam al-Nasafi - Syed Abdul Rahman, Syed Mohammad Hilmi; al-Amoush, Bassam; Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
How does nature exist? Who created it? Is it made out of nothing? What is the proof that nature is impermanence (hadith)? Is it compulsory to recognize this nature as huduth through logic and sensible nature? This article discusses impermanence of nature according to al-Imam al-Nasafi and the argument he applied to prove it. The article concludes that nature according to him is hadith through the method of al-jawahir wa al-a’rad. Although this method is opposed by some scholars arguing that it is not found in the Qur’an and Hadith, nor it is used by the scholars of salaf, the mutakallimin said that this method is actually derived from the conclusion of verse 76, Surah al-An‘am: “So when the night covered him [with darkness], he saw a star. He said, “This is my lord.” But when it set, he said, “I like not those that disappear.” In this verse, Prophet Ibrahim a.s argued with the star-set as a proposition that the star was changed and hadith. Hence, this huduth al-ajsam become an argument that the nature is hadith based on the words of Prophet Ibrahim a.s as mentioned above: “I like not those that disappear.” According to mutakallimin, something that can come and go has static and moving nature which indicates both characteristics are muhdath (new). Therefore, this nature is created and muhdath.